An underground high impermeability durable concrete

CN117800668BActive Publication Date: 2026-10-16SUZHOU SHANGJIAN HANGXIN CONCRETE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311510217.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-14
Publication Date
2026-10-16
Estimated Expiration
2043-11-14

AI Technical Summary

Technical Problem

但由于水泥浆中的细小孔隙不能完全封堵,导致混凝土的抗渗性和抗冻性劣化

Benefits of technology

[0023]1. This invention uses water-absorbing and expanding rubber mixed with silica fume as a filler for underground concrete, which is often in a damp state. The water-absorbing and expanding rubber mixed with silica fume can absorb water and expand at the same time, filling the pores in the concrete and blocking the formed seepage channels, thereby achieving the effect of impermeability. On the other hand, the water-absorbing and expanding rubber also contains silica fume. As water is absorbed, the silica fume will overflow from the water-absorbing and expanding rubber into the concrete and fill the gaps in the transition zone between cement stone and interface, thereby improving the interface structure between the water-absorbing and expanding rubber and cement stone, making the material structure more compact, and further blocking the possible seepage channels.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application provides a kind of underground high impermeability durability concrete. Including the following components: cement 50 parts, coarse aggregate 100-110 parts, polycarboxylate superplasticizer 1.2-1.5 parts, modified machine-made sand 74-76 parts, water-absorbing swelling rubber mixed with silica powder 7-10 parts. The application uses water-absorbing swelling rubber mixed with silica powder as filler, which is used for underground concrete, often in a humid state. Water-absorbing swelling rubber mixed with silica powder can adsorb water and expand at the same time, filling the pores in the concrete and blocking the formation of permeation channels, thereby achieving the effect of impermeability. On the other hand, water-absorbing swelling rubber also contains silica powder. With the adsorption of water, silica powder will overflow from the water-absorbing swelling rubber into the concrete, filling the voids between the cement stone and the interface transition zone, improving the interface structure between the water-absorbing swelling rubber and the cement stone, and making the material structure more dense, further blocking the possible formation of permeation channels.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building materials technology, specifically to a type of underground high-permeability and durable concrete. Background Technology

[0002] Impermeability and frost resistance are two crucial aspects of concrete durability, their quality primarily depending on the porosity, pore size, and pore characteristics within the concrete. Concrete is a plastic mixture formed by adding water to cement, fine aggregate, and coarse aggregate. It is an artificial stone material formed by sealing the pores in the mortar with cement paste and filling the gaps in the coarse aggregate with mortar, then hardening. However, because the tiny pores in the cement paste cannot be completely sealed, the impermeability and frost resistance of concrete deteriorate. Currently, the main measures to improve the impermeability and frost resistance of concrete include adding admixtures (crack-resistant and impermeable agents, etc.) and organic materials such as asphalt, acrylic emulsion, and epoxy, but the modification effects are not yet satisfactory. Therefore, how to provide more suitable fillers to improve the impermeability of concrete, especially concrete suitable for underground construction materials, is an urgent problem to be solved. Summary of the Invention

[0003] Technical Problem to be Solved: To address the aforementioned technical problems, the purpose of this invention is to provide a highly impermeable and durable underground concrete. This concrete utilizes water-absorbing and expanding rubber mixed with silica fume as a filler. Underground concrete is often in a damp state. The water-absorbing and expanding rubber mixed with silica fume can absorb water and expand, filling the pores in the concrete and blocking any potential seepage pathways, thus achieving an impermeable effect. Furthermore, the water-absorbing and expanding rubber also contains silica fume. As water is absorbed, the silica fume overflows from the rubber into the concrete, filling the gaps in the transition zone between the cement paste and the cement paste. This improves the interface structure between the water-absorbing and expanding rubber and the cement paste, making the material structure more compact and further blocking any potential seepage pathways.

[0004] Technical solution: A type of underground high impermeability and durability concrete, comprising the following components by weight: 50 parts cement, 100-110 parts coarse aggregate, 1.2-1.5 parts polycarboxylate superplasticizer, 74-76 parts modified manufactured sand, and 7-10 parts water-absorbing and expanding rubber mixed with silica fume.

[0005] Preferably, the cement is silicate cement with a strength grade of ≥44.0.

[0006] Preferably, the coarse aggregate is 5-20mm continuous-sized crushed stone.

[0007] Preferably, in the coarse aggregate, 5-10mm crushed stone accounts for 40 wt.%, 10-15mm crushed stone accounts for 30 wt.%, and 15-20mm crushed stone accounts for 30 wt.%.

[0008] Preferably, the polycarboxylate superplasticizer has a solid content of 18%.

[0009] Preferably, the method for preparing the modified manufactured sand is as follows:

[0010] S1: Mix the silicone-based waterproofing agent and the cationic clay anti-swelling agent to prepare a mixed solution;

[0011] S2: Spread the dried manufactured sand evenly in a container, and spray the mixed solution onto it in four times with a spray bottle until it is evenly mixed and there are no obvious lumps.

[0012] S3: Let stand at room temperature for 4 hours, then dry in a 60℃ oven and cool to obtain the product.

[0013] Preferably, the mass ratio of the silicone-based waterproofing agent to the cationic clay anti-swelling agent in S1 is 6:4.

[0014] Preferably, the amount of the mixed solution in S2 is 1.5‰ of the mass of the manufactured sand.

[0015] Preferably, the particle size of the water-absorbing and swelling rubber doped with silica powder is 3-5 mm.

[0016] Preferably, the method for preparing the water-absorbing and swelling rubber doped with silica powder is as follows:

[0017] Step 1: Take 5 mL of acrylic acid and neutralize it to 70% with 18% NaOH solution under ice-water bath;

[0018] Step 2: Add 0.1g of initiator ammonium persulfate, and add 0.5-1g of thiophanate-methyl polysaccharide while stirring vigorously. After the system is homogeneous, add microsilica powder with a particle size ≤300nm and stir evenly.

[0019] Step 3: Place in a microwave oven and turn on the microwave to carry out the graft copolymerization reaction;

[0020] Step 4: After the reaction is complete, remove the sample and dry it under vacuum at room temperature to obtain the final product.

[0021] Preferably, in step 3, the microwave radiation power is 180W and the radiation time is 3s.

[0022] Beneficial effects:

[0023] 1. This invention uses water-absorbing and expanding rubber mixed with silica fume as a filler for underground concrete, which is often in a damp state. The water-absorbing and expanding rubber mixed with silica fume can absorb water and expand at the same time, filling the pores in the concrete and blocking the formed seepage channels, thereby achieving the effect of impermeability. On the other hand, the water-absorbing and expanding rubber also contains silica fume. As water is absorbed, the silica fume will overflow from the water-absorbing and expanding rubber into the concrete and fill the gaps in the transition zone between cement stone and interface, thereby improving the interface structure between the water-absorbing and expanding rubber and cement stone, making the material structure more compact, and further blocking the possible seepage channels.

[0024] 2. When water cannot penetrate into the concrete, the amount of water that can be frozen inside the concrete is relatively scarce. Therefore, under the conditions of freeze-thaw cycles, the frost resistance of the concrete is greatly improved, thereby enhancing its durability.

[0025] 3. This invention uses a silicon-based waterproofing agent and a clay anti-swelling agent as two-component surface modifiers. The waterproofing agent forms a hydrophobic layer on the surface of manufactured sand and clay, while the cationic clay anti-swelling agent can effectively inhibit the hydration and expansion of clay, reduce the adsorption sites of polycarboxylate superplasticizer, and reduce the adverse effects of the mud powder content in manufactured sand on the workability of concrete. Detailed Implementation

[0026] This invention proposes a high-permeability and durable underground concrete. To make the objectives, technical solutions, and effects of this invention clearer and more explicit, the following will provide a more detailed description of the invention with reference to specific embodiments. It should be understood that the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention.

[0027] Example 1

[0028] The preparation method of modified manufactured sand is as follows:

[0029] S1: Mix silicone-based waterproofing agent and cationic clay anti-swelling agent in a mass ratio of 6:4 to prepare a mixed solution;

[0030] S2: Spread the dried manufactured sand evenly in a container, and spray the mixed solution onto it in four batches using a spray bottle. Mix evenly without obvious lumps. The amount of mixed solution used is 1.5‰ of the mass of the manufactured sand.

[0031] S3: Let stand at room temperature for 4 hours, then dry in a 60℃ oven and cool to obtain the product.

[0032] Example 2

[0033] The preparation method of water-absorbing and swelling rubber doped with silica powder is as follows:

[0034] Step 1: Take 5 mL of acrylic acid and neutralize it to 70% with 18% NaOH solution under ice-water bath;

[0035] Step 2: Add 0.1g of initiator ammonium persulfate, and add 0.5g of blastocysteine ​​polysaccharide while stirring vigorously. After the system is homogeneous, add silica powder with a particle size ≤300nm and stir evenly.

[0036] Step 3: Place it in a microwave oven and turn on the microwave oven to carry out the graft copolymerization reaction. The microwave radiation power is 180W and the radiation time is 3s.

[0037] Step 4: After the reaction is complete, remove the sample and dry it under vacuum at room temperature to obtain the final product.

[0038] Example 3

[0039] The preparation method of water-absorbing and swelling rubber doped with silica powder is as follows:

[0040] Step 1: Take 5 mL of acrylic acid and neutralize it to 70% with 18% NaOH solution under ice-water bath;

[0041] Step 2: Add 0.1g of initiator ammonium persulfate, and add 0.6g of blastocysteine ​​polysaccharide while stirring vigorously. After the system is homogeneous, add microsilica powder with a particle size ≤300nm and stir evenly.

[0042] Step 3: Place it in a microwave oven and turn on the microwave oven to carry out the graft copolymerization reaction. The microwave radiation power is 180W and the radiation time is 3s.

[0043] Step 4: After the reaction is complete, remove the sample and dry it under vacuum at room temperature to obtain the final product.

[0044] Example 4

[0045] The preparation method of water-absorbing and swelling rubber doped with silica powder is as follows:

[0046] Step 1: Take 5 mL of acrylic acid and neutralize it to 70% with 18% NaOH solution under ice-water bath;

[0047] Step 2: Add 0.1g of initiator ammonium persulfate, and add 0.7g of blastocysteine ​​polysaccharide while stirring vigorously. After the system is homogeneous, add silica powder with a particle size ≤300nm and stir evenly.

[0048] Step 3: Place it in a microwave oven and turn on the microwave oven to carry out the graft copolymerization reaction. The microwave radiation power is 180W and the radiation time is 3s.

[0049] Step 4: After the reaction is complete, remove the sample and dry it under vacuum at room temperature to obtain the final product.

[0050] Example 5

[0051] The preparation method of water-absorbing and swelling rubber doped with silica powder is as follows:

[0052] Step 1: Take 5 mL of acrylic acid and neutralize it to 70% with 18% NaOH solution under ice-water bath;

[0053] Step 2: Add 0.1g of initiator ammonium persulfate, and add 0.8g of blastocysteine ​​polysaccharide while stirring vigorously. After the system is homogeneous, add microsilica powder with a particle size ≤300nm and stir evenly.

[0054] Step 3: Place it in a microwave oven and turn on the microwave oven to carry out the graft copolymerization reaction. The microwave radiation power is 180W and the radiation time is 3s.

[0055] Step 4: After the reaction is complete, remove the sample and dry it under vacuum at room temperature to obtain the final product.

[0056] Example 6

[0057] The preparation method of water-absorbing and swelling rubber doped with silica powder is as follows:

[0058] Step 1: Take 5 mL of acrylic acid and neutralize it to 70% with 18% NaOH solution under ice-water bath;

[0059] Step 2: Add 0.1g of initiator ammonium persulfate, and add 0.9g of thiophanate-methyl polysaccharide while stirring vigorously. After the system is homogeneous, add silica powder with a particle size ≤300nm and stir until homogeneous.

[0060] Step 3: Place it in a microwave oven and turn on the microwave oven to carry out the graft copolymerization reaction. The microwave radiation power is 180W and the radiation time is 3s.

[0061] Step 4: After the reaction is complete, remove the sample and dry it under vacuum at room temperature to obtain the final product.

[0062] Example 7

[0063] The preparation method of water-absorbing and swelling rubber doped with silica powder is as follows:

[0064] Step 1: Take 5 mL of acrylic acid and neutralize it to 70% with 18% NaOH solution under ice-water bath;

[0065] Step 2: Add 0.1g of initiator ammonium persulfate, add 1g of blastocysteine ​​polysaccharide while stirring vigorously, and after the system is homogeneous, add microsilica powder with a particle size ≤300nm and stir evenly;

[0066] Step 3: Place it in a microwave oven and turn on the microwave oven to carry out the graft copolymerization reaction. The microwave radiation power is 180W and the radiation time is 3s.

[0067] Step 4: After the reaction is complete, remove the sample and dry it under vacuum at room temperature to obtain the final product.

[0068]

[0069]

[0070] Based on the comparison of water absorption rate and swelling rate in Examples 2-7, the water-absorbing and swelling rubber doped with silica powder prepared in Example 6 was selected for subsequent tests.

[0071] Example 8

[0072] A type of underground high-permeability and durable concrete, by weight, comprises the following components: 50 parts cement, 110 parts coarse aggregate, 1.5 parts polycarboxylate superplasticizer, 76 parts modified manufactured sand, and 7 parts water-absorbing and expanding rubber with a particle size of 3-5 mm and mixed with silica fume; wherein the cement is silicate cement with a strength grade ≥44.0; the coarse aggregate consists of 40 wt.% 5-10 mm crushed stone, 30 wt.% 10-15 mm crushed stone, and 30 wt.% 15-20 mm crushed stone; the polycarboxylate superplasticizer has a solid content of 18%.

[0073] To use, mix 200 parts water with the above ingredients.

[0074] Example 9

[0075] A type of underground high-permeability and durable concrete, by weight, comprises the following components: 50 parts cement, 110 parts coarse aggregate, 1.5 parts polycarboxylate superplasticizer, 76 parts modified manufactured sand, and 8 parts water-absorbing and expanding rubber with a particle size of 3-5 mm and mixed with silica fume; wherein the cement is silicate cement with a strength grade ≥44.0; the coarse aggregate consists of 40 wt.% 5-10 mm crushed stone, 30 wt.% 10-15 mm crushed stone, and 30 wt.% 15-20 mm crushed stone; the polycarboxylate superplasticizer has a solid content of 18%.

[0076] To use, mix 200 parts water with the above ingredients.

[0077] Example 10

[0078] A type of underground high-permeability and durable concrete, by weight, comprises the following components: 50 parts cement, 110 parts coarse aggregate, 1.5 parts polycarboxylate superplasticizer, 76 parts modified manufactured sand, and 9 parts water-absorbing and expanding rubber with a particle size of 3-5 mm and mixed with silica fume; wherein the cement is silicate cement with a strength grade ≥44.0; the coarse aggregate consists of 40 wt.% 5-10 mm crushed stone, 30 wt.% 10-15 mm crushed stone, and 30 wt.% 15-20 mm crushed stone; the polycarboxylate superplasticizer has a solid content of 18%.

[0079] To use, mix 200 parts water with the above ingredients.

[0080] Example 11

[0081] A type of underground high-permeability and durable concrete, by weight, comprises the following components: 50 parts cement, 110 parts coarse aggregate, 1.5 parts polycarboxylate superplasticizer, 76 parts modified manufactured sand, and 10 parts water-absorbing and expanding rubber with a particle size of 3-5 mm and mixed with silica fume; wherein the cement is silicate cement with a strength grade ≥44.0; the coarse aggregate consists of 40 wt.% 5-10 mm crushed stone, 30 wt.% 10-15 mm crushed stone, and 30 wt.% 15-20 mm crushed stone; the polycarboxylate superplasticizer has a solid content of 18%.

[0082] To use, mix 200 parts water with the above ingredients.

[0083] Example 12

[0084] A type of underground high-permeability and durable concrete, by weight, comprises the following components: 50 parts cement, 110 parts coarse aggregate, 1.5 parts polycarboxylate superplasticizer, 74 parts modified manufactured sand, and 9 parts water-absorbing and expanding rubber with a particle size of 3-5 mm and mixed with silica fume; wherein the cement is silicate cement with a strength grade ≥44.0; the coarse aggregate consists of 40 wt.% 5-10 mm crushed stone, 30 wt.% 10-15 mm crushed stone, and 30 wt.% 15-20 mm crushed stone; the polycarboxylate superplasticizer has a solid content of 18%.

[0085] To use, mix 200 parts water with the above ingredients.

[0086] Example 13

[0087] A type of underground high-permeability and durable concrete, by weight, comprises the following components: 50 parts cement, 110 parts coarse aggregate, 1.5 parts polycarboxylate superplasticizer, 75 parts modified manufactured sand, and 9 parts water-absorbing and expanding rubber with a particle size of 3-5 mm and mixed with silica fume; wherein the cement is silicate cement with a strength grade ≥44.0; the coarse aggregate consists of 40 wt.% 5-10 mm crushed stone, 30 wt.% 10-15 mm crushed stone, and 30 wt.% 15-20 mm crushed stone; the polycarboxylate superplasticizer has a solid content of 18%.

[0088] To use, mix 200 parts water with the above ingredients.

[0089] Example 14

[0090] A type of underground high-permeability and durable concrete, by weight, comprises the following components: 50 parts cement, 110 parts coarse aggregate, 1.5 parts polycarboxylate superplasticizer, 76 parts modified manufactured sand, and 9 parts water-absorbing and expanding rubber with a particle size of 3-5 mm and mixed with silica fume; wherein the cement is silicate cement with a strength grade ≥44.0; the coarse aggregate consists of 30 wt.% 5-10 mm crushed stone, 40 wt.% 10-15 mm crushed stone, and 30 wt.% 15-20 mm crushed stone; the polycarboxylate superplasticizer has a solid content of 18%.

[0091] To use, mix 200 parts water with the above ingredients.

[0092] Example 15

[0093] A type of underground high-permeability and durable concrete, by weight, comprises the following components: 50 parts cement, 110 parts coarse aggregate, 1.5 parts polycarboxylate superplasticizer, 76 parts modified manufactured sand, and 9 parts water-absorbing and expanding rubber with a particle size of 3-5 mm and mixed with silica fume; wherein the cement is silicate cement with a strength grade ≥44.0; the coarse aggregate consists of 30 wt.% 5-10 mm crushed stone, 30 wt.% 10-15 mm crushed stone, and 40 wt.% 15-20 mm crushed stone; the polycarboxylate superplasticizer has a solid content of 18%.

[0094] To use, mix 200 parts water with the above ingredients.

[0095] Comparative Example 1

[0096] The difference between this embodiment and Embodiment 10 is that water-absorbing and swelling rubber without silica powder is used.

[0097] Comparative Example 2

[0098] Compared with Example 10, this embodiment does not use water-absorbing and swelling rubber containing silica powder, but adds an equal amount of silica powder. Specifically:

[0099] A type of underground high-permeability and durable concrete, by weight, comprises the following components: 50 parts cement, 110 parts coarse aggregate, 1.5 parts polycarboxylate superplasticizer, 76 parts modified manufactured sand, and 9 parts silica fume; wherein the cement is silicate cement with a strength grade ≥44.0; the coarse aggregate consists of 40 wt.% 5-10mm crushed stone, 30 wt.% 10-15mm crushed stone, and 30 wt.% 15-20mm crushed stone; the polycarboxylate superplasticizer has a solid content of 18%.

[0100] To use, mix 200 parts water with the above ingredients.

[0101] Prepare non-standard cubic test blocks of 100mm×100mm×100mm;

[0102] The water penetration resistance of rubber lightweight aggregate concrete was tested using the penetration height method. According to the provisions of SL352-2020 "Test Procedure for Hydraulic Concrete", the single pressurization method was used. After constant pressure stabilization for 24 hours, the concrete specimens were split open, and the water penetration height of each group of specimens was measured. The average value was taken to represent the water penetration resistance of the concrete.

[0103] Freeze-thaw resistance tests were conducted using the rapid freezing method, with 50, 100, and 200 freeze-thaw cycles respectively. The results are shown in Tables 1 and 2 below:

[0104] Table 1

[0105] Example 8 9.42 Example 9 9.16 Example 10 8.87 Example 11 8.84 Example 12 9.79 Example 13 9.43 Example 14 8.96 Example 15 8.93 Comparative Example 1 78.6 Comparative Example 2 35.9

[0106] Table 2

[0107]

[0108]

Claims

1. A type of underground high-permeability and durable concrete, characterized in that, By weight, it includes the following components: 50 parts cement, 100-110 parts coarse aggregate, 1.2-1.5 parts polycarboxylate superplasticizer, 74-76 parts modified manufactured sand, and 7-10 parts water-absorbing and expanding rubber mixed with silica fume. The method for preparing the modified manufactured sand is as follows: S1: Mix the silicone-based waterproofing agent and the cationic clay anti-swelling agent to prepare a mixed solution; S2: Spread the dried manufactured sand evenly in a container, and spray the mixed solution onto it in four times with a spray bottle until it is evenly mixed and there are no obvious lumps. S3: Let stand at room temperature for 4 hours, then dry in a 60℃ oven and cool to obtain the product; The method for preparing the water-absorbing and swelling rubber doped with silica powder is as follows: Step 1: Take 5 mL of acrylic acid and neutralize it to 70% with 18% NaOH solution under ice-water bath; Step 2: Add 0.1g of initiator ammonium persulfate, and add 0.5-1g of thiophanate-methyl polysaccharide while stirring vigorously. After the system is homogeneous, add silica powder with a particle size ≤300nm and stir evenly. Step 3: Place in a microwave oven and turn on the microwave to carry out the graft copolymerization reaction; Step 4: After the reaction is complete, remove and vacuum dry at room temperature to obtain the product; The mass ratio of the silicon-based waterproofing agent to the cationic clay anti-swelling agent in S1 is 6:4; The amount of the mixed solution used in S2 is 1.5‰ of the mass of the manufactured sand; In step 3, the microwave radiation power is 180W and the radiation time is 3s.

2. The underground high impermeability and durability concrete according to claim 1, characterized in that, The coarse aggregate is 5-20mm continuous-sized crushed stone.

3. The underground high impermeability and durability concrete according to claim 1, characterized in that, In the coarse aggregate, 5-10mm crushed stone accounts for 40 wt.%, 10-15mm crushed stone accounts for 30 wt.%, and 15-20mm crushed stone accounts for 30 wt.%.

4. The underground high impermeability and durability concrete according to claim 1, characterized in that, The polycarboxylate superplasticizer has a solid content of 18%.

5. The underground high impermeability and durability concrete according to claim 1, characterized in that, The particle size of the water-absorbing and swelling rubber doped with silica powder is 3-5 mm.

Citation Information

Patent Citations

  • Highly-impervious concrete and preparation method thereof

    CN109279846A

  • Two-component modifier modified machine-made sand and preparation method thereof

    CN114573261A